A dynamic pre-travel error prediction model for the kinematic touch trigger probe. (November 2019) - Li, Yamin; Zeng, Long; Tang, Kai; Li, Simi
Highlights: A dynamic pre-travel error model for kinematic touch trigger probe is proposed. The model is adequately validated by conducting experimental tests. Factors that could affect the pre-travel error are analysed by using the model. Abstract: Kinematic touch trigger probe (KTTP) has been widely used in dimensional measurement owing to its high reliability and low cost. However, its pre-travel error, which is inherent by its nature, often severely affects the measuring accuracy. Most of the existing models for predicting the pre-travel error are static and completely ignore the dynamics of the measuring process and thus lack the predicting accuracy. This paper presents a dynamic model for KTTP which is able to accurately describe the measuring process in the time domain. In our model, the probe stylus is modelled as a chain of rigid body elements (RBEs) connected by imaginary springs. By establishing the corresponding dynamic differential equations and solving them, we are able to obtain the correct triggering time interval between the moment when the stylus contacts the object and the time when at least one of the contact forces between the support balls and the pedestal rods reaches zero, and consequently the pre-travel error by multiplying it with the given measuring speed. Calibration tests performed by us have shown a good agreement between our model and the physical measuring results. With the model validated, we further used it to analyse various factors that could affect the pre-travel error, such as the probe design parameters, the measuring speed, and the gravitational force, and the findings from the analysis are also reported in this paper.